International relations theories : discipline and diversity - Dunne, Timothy, 1965-; Kurki, Milja, 1978-; Kušić, Katarina; Smith, Steve, 1952- (Oxford University Press, 2024)
Unrivalled coverage of IR theories from leading experts, including historically dominant traditions such as realism, and liberalism, to theories such as postcolonialism and green theory. Featuring a new organisation to reflect the importance and focus on global IR as well as newly authored chapters on classical realism, liberalism, Marxism, and critical theories. A wide range of case studies show readers how theory can be applied to address concrete political problems. Key Features: · Expert line-up of contributors offer coverage of dominant and emerging theories and arguments from diverse perspectives · Includes coverage of historically marginalised theories, including postcolonialism and environmentalism · A case study in each chapter shows how theory can be used to explain real-world problems and dilemmas and additional questions to encourage students to analyse and evaluate the different theories for themselves · Boxes highlighting key books or articles introduce students to prominent works in the field to encourage wider reading and research interests · Spotlights on key books and articles encourage readers to go beyond the textbook and develop their research interests, exploring important works in the field.